The Influence of Price, Location and Word Of Mouth on Purchasing Decisions at Green Resto - Ananda, Anggita Putri; Sari, Anita Kartika; Fatchurrohman, Mochamad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2023)
The rise of marketing activities in the MSME (Micro, Small and Medium Enterprises) sector is something that is familiar even though it is inseparable from competition in the business world. Consumer purchasing decisions are important for SMEs, one of which is the Green Resto restaurant in Surabaya. This study measures the extent to which Purchase Decisions can be measured through the variables Price, Location, and Word of Mouth. This research is a quantitative research using multiple linear regression data analysis techniques assisted by the SPSS 25 program. The data from this study were taken from the results of questionnaires distributed to 97 respondents who are customers of Green Resto. The results showed that Price, Location and Word of Mouth had a partial or simultaneous and significant effect on purchasing decisions at Green Resto. Where the price has a partial and significant effect on purchasing decisions at Green Resto. Location has a partial and significant effect on purchasing decisions at Green Resto. Word of Mouth has a partial and significant effect on purchasing decisions at Green Resto. And as a whole it can be said that Price, Location and Word of Mouth have a simultaneous and significant effect on purchasing decisions at Green Resto.